Znaczenie wykazu akt w procesie brakowania i niszczenia dokumentacji operacyjnej Służby Bezpieczeństwa w latach 1956–1989. Zarys problematyki - Koller, Stanisław (Przegląd Archiwalny Instytutu Pamięci Narodowej, 2023)
The mass destruction of the archival materials by the Security Services in the years from 1989 to 1990, i.e. after the Round Table Arrangements provoked the society, opposition and journalistic circles to express their loud objection. Under the pressure of the mass press campaign on 31 January 1990 the Minister of Internal Affairs forbade to destroy the documents in the Ministry of Internal Affairs, including the archival documents that were attempted to get rid of contrary to the regulations of the Ministry of Internal Affairs. The author discusses the ordinance of the Minister of Internal Affairs from the years from 1956 to 1989 regulating the procedures with the materials created in the operational units of the Security Services. The objective of the article is an attempt to answer the basic questions regarding the ways and causes of destroying the documents by the Security Services, among others: what the attitude of the ministry to created operational files was, which operational materials were subject to storage and which ones were the subject to destruction, which were the criteria that the Ministry had during establishing the category of period of storing the operational documents, why they were destroyed and what were the grounds as well as the question whether sorting and destruction of the materials prepared by the Security Services was of the political nature in the People’s Republic of Poland.